The Influence Of Trust To Digital Influencer, Social Media, Halal Brand Awareness On Purchase Intention On Azarine Sunscreen With Attitude Toward Digital Marketing As An Intervening Variable - saifuddin saifuddin; Laila Isnawati Sholihah (Institut Agama Islam Negeri Palopo, 2024)
To find out the involvement of attitudes towards digital marketing mediating trust in digital influencers, social media, halal product awareness towards purchase intention. The object of this study is Sunscreen Azarine with 382 respondents living in Klego Boyolali. This study uses a quantitative method with data obtained from the results of distributing questionnaires. The tool to complete this research is SPSS statistics version 25. The findings of the study indicate that trust to digital influencers, social media, halal brand awareness has a significant positive effect on purchase intention. Attitude toward digital marketing does not affect purchase intention but can mediate independent and dependent variables.